2020
DOI: 10.1007/s10840-019-00692-y
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of ACHD patients with non-inducible versus inducible IART undergoing cavo-tricuspid isthmus ablation: the role of empiric ablation

Abstract: Background: Catheter ablation for supraventricular tachycardia (SVT) in adults with congenital heart disease (ACHD) is an important therapeutic option. Cavotricuspid isthmus (CTI) dependent intra-atrial re-entrant tachycardia (IART) is common. However, induction of sustained tachycardia at the time of ablation is not always possible. We hypothesised that performing an empiric CTI line in case of noninducibility leads to good outcomes.Objectives: Long-term outcomes of empiric versus entrained CTI ablation in CH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…In routine practice, empirical CTI ablation was adopted if the tachycardia was judged as typical CTI‐AFL by ECG analysis before procedure. Sawhney et al 18 has shown that long‐term outcomes (over 7 years) after empiric and entrained CTI ablation for CTI‐AFL are comparable. Hence, an empiric CTI line should be considered in the case of noninducibility of CTI‐AFL.…”
Section: Discussionmentioning
confidence: 99%
“…In routine practice, empirical CTI ablation was adopted if the tachycardia was judged as typical CTI‐AFL by ECG analysis before procedure. Sawhney et al 18 has shown that long‐term outcomes (over 7 years) after empiric and entrained CTI ablation for CTI‐AFL are comparable. Hence, an empiric CTI line should be considered in the case of noninducibility of CTI‐AFL.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas ablation of the flutter circuit is indicated in patients with documented AFL, it is often considered in those without a documented AFL history, but high risk of unrecognized AFL or development of AFL in the future 5 . The practice of empiric flutter ablation is employed to prevent symptomatic recurrence and attenuate stroke risk in a group that may eventually present with thromboembolic complications as the first indication of AFL 6,7 . A simple diagnostic maneuver to determine the existence of a potential AFL circuit, and therefore a risk of occult or future AFL, would be very useful.…”
Section: Introductionmentioning
confidence: 99%
“…5 The practice of empiric flutter ablation is employed to prevent symptomatic recurrence and attenuate stroke risk in a group that may eventually present with thromboembolic complications as the first indication of AFL. 6,7 A simple diagnostic maneuver to determine the existence of a potential AFL circuit, and therefore a risk of occult or future AFL, would be very useful. This could support the decision on whether to empirically ablate a flutter circuit at time of ablation for other rhythms, such as atrial fibrillation.…”
Section: Introductionmentioning
confidence: 99%